Peran Kepala Sekolah dalam Meningkatkan Kualitas Pembelajaran - Nurhayati Nurhayati; Annisa Rahmadani (Journal on Education, 2023)
Implementing extracurricular activities into the classroom has been shown to improve students' abilities in a number of areas and have a positive impact on their academic performance. School autonomy refers to the process of delegating decision-making power to schools and encouraging student input into policy. The principal's job as an educator is to improve the quality of education by directing training and coaching efforts both to students and education personnel. The principal's supervisory responsibilities include, the development of academic supervision programs designed to raise the professional standards of educators, and actually supervising teachers in the classroom in an effective manner. Al-Azhar Flagship High School in Medan became the venue for this research. The student is the object of this study, while the principal and the teacher involved are the subjects. Primary data sources and secondary data sources are used by researchers. The findings suggest that the principal at Al-Azhar High School played a role in improving the quality of education there. Students are actively involved in classroom learning and extracurricular activities show excellent quality. Teachers take an active role in designing and creating engaging lessons for their students. The leadership of the principal at Al-Azhar High School Medan can be seen from the progress of the school in achieving the school's vision of becoming an intellectual Muslim and Muslim intellectual, as well as improving the quality of education it organizes.